Answer:
The number that goes in place of the question mark is 2.
Step-by-step explanation:
Let's solve it!
3x² + 12x - 24 = 0
First we can factor 3 out of each term:
x² + 4x - 8 = 0
Now we'll add 12 to both sides to complete the square:
x² + 4x + 4 = 12
And finish it off:
(x + 2)² = 12
So the answer to the question is 2
Bonus:
We can also now solve this for x:
(x + 2)² = 12
x = √12 - 2
x = 2√3 - 2
x ≈ 2 × ±1.732 - 2
x ≈ 1.464, -5.464
Combine like terms to simplify an expression. For example, all terms with the variable x can be combined into one term. All constants can also be combined.
1) -4x - 10x = -14x
2) -r - 10r = -11r
3) -2x + 11 +6x = 4x + 11
4) 11r - 12r = -r
5) -v + 12v = 11v
6) -8x - 11x = -19x
7) 4p + 2p = 6p
8) 5n + 11n = 16n
9) n + 4 - 9 - 5n = -4n - 5
10) 12r + 5 + 3r - 5 = 15r (the 5 and -5 cancel each other out)
11) -5 + 9n + 6 = 9n + 1
Answer:
5:3
Step-by-step explanation:
When the ratio says x:y=5:1, it means that x is 5 times greater than y. So, plug in 5 for x and 1 for y.
4(5)+5(1):3(5)
20+5:15
25:15 , if simplified then the ratio 5:3
Answer:
h > 24
Step-by-step explanation:
h/3 > 8
so basially you move the number three from the left side to the right side
so from division to multiplication
h > 8 x 3
h > 24
Solved !
Hope it helped ! Have a nice day !
Answer:3. B 4. B
Step-by-step explanation:3. Supplementary equals 180, 113 + 67 = 180